IMO functional equations

Algebra Level 4

R + \mathbb R^+ denotes the set of all positive real numbers. There exists only one function f : R + R + f : \mathbb {R^+ \to R^+} which satisfies

x f ( x 2 ) f ( f ( y ) ) + f ( y f ( x ) ) = f ( x y ) ( f ( f ( x 2 ) ) + f ( f ( y 2 ) ) ) \large\ \\ xf\left(x^2\right) f\left( f(y)\right) + f\left( yf(x) \right) = f(xy) \left( f\left( f\left(x^2 \right) \right) + f\left( f\left(y^2\right)\right)\right)

for all positive real numbers x x and y y .

Then find the numerical value of f ( 1 2017 ) \large\ f\left( \frac { 1 }{ 2017 } \right) .


The answer is 2017.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jul 25, 2017

To get the ball rolling, here is a partial proof, assuming that the function f f is continuous at 1 1 .

Putting x = y = 1 x=y=1 gives f ( 1 ) f f ( 1 ) + f f ( 1 ) = f ( 1 ) [ f f ( 1 ) + f f ( 1 ) ] = 2 f ( 1 ) f f ( 1 ) f(1)\,ff(1) + ff(1) \;= \; f(1)[ff(1) + ff(1)] \;=\; 2f(1)\,ff(1) and so f ( 1 ) = 1 f(1) = 1 . Putting x = 1 x=1 gives f f ( y ) + f ( y ) = f ( y ) [ 1 + f f ( y 2 ) ] ff(y) + f(y) \; = \; f(y)[1 + ff(y^2)] for y > 0 y > 0 . Putting y = 1 y=1 gives x f ( x 2 ) + f f ( x ) = f ( x ) [ f f ( x 2 ) + 1 ] x f(x^2) + ff(x) \; = \; f(x)[ff(x^2) + 1] for x > 0 x > 0 . But this implies that x f ( x 2 ) + f f ( x ) = f f ( x ) + f ( x ) xf(x^2) + ff(x) \; = \; ff(x) + f(x) for all x > 0 x > 0 , so that x f ( x 2 ) = f ( x ) xf(x^2) = f(x) for all x > 0 x > 0 . Thus g ( x ) = x f ( x ) g(x) = xf(x) is such that g ( x 2 ) = g ( x ) g(x^2) = g(x) for all x > 0 x > 0 .

Assuming that f f is continuous at 1 1 , we deduce that g g is continuous at 1 1 . Since g ( x ) = g ( x 2 n ) n 1 g(x) \; = \; g\big(\sqrt[2^n]{x}\big) \hspace{2cm} n \ge 1 we see, letting n n \to \infty , that g ( x ) = g ( 1 ) = 1 g(x) = g(1) = 1 for all x > 0 x > 0 . Thus f ( x ) = x 1 f(x) = x^{-1} for all x > 0 x > 0 , making the answer 2017 \boxed{2017} (again).

@Mark Hennings ,

Great job sir. Mine uses establishing the injectivity of the function.

Priyanshu Mishra - 3 years, 10 months ago

Log in to reply

Please post it...

Mark Hennings - 3 years, 10 months ago

Log in to reply

OK THEN. I will post it.

Priyanshu Mishra - 3 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...